2013
DOI: 10.3109/0886022x.2012.761040
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Montelukast Which Is Cysteinyl-Leukotriene Receptor Antagonist on Gentamicin-Induced Nephrotoxicity and Oxidative Damage in Rat Kidney

Abstract: Nephrotoxicity is a major complication of gentamicin (GEN). We aimed to evaluate the potential protective effect of montelukast (MK) against GEN-induced nephrotoxicity in rats. Thirty-two rats were randomly divided into four groups, each consisting of eight animals as follows: (1) the rats were control; (2) intraperitoneally injected with GEN 14 consecutive days (100 mg/kg/day); (3) treated with GEN plus distilled water via nasogastric gavage for 14 days; and (4) treated with GEN plus MK (10 mg/kg/day) for 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 47 publications
4
27
1
Order By: Relevance
“…Although regular montelukast treatment can improve some asthma outcomes compared to placebo, it does not reduce the frequency of hospitalization, courses of prednisone or the number of symptom-free days in children with recurrent, viral-induced wheezing [1]. Animal studies show that montelukast has a beneficial effect on oxidative stress-mediated conditions like ischemia-reperfusion injury [32], drug intoxication [33,34] and lipopolysaccharide-induced oxidative stress [35]. Al Saadi et al [25 ]reported that montelukast decreased the ROS production in the whole blood and in isolated human polymorphonuclear neutrophils in asthmatic children.…”
Section: Discussionmentioning
confidence: 99%
“…Although regular montelukast treatment can improve some asthma outcomes compared to placebo, it does not reduce the frequency of hospitalization, courses of prednisone or the number of symptom-free days in children with recurrent, viral-induced wheezing [1]. Animal studies show that montelukast has a beneficial effect on oxidative stress-mediated conditions like ischemia-reperfusion injury [32], drug intoxication [33,34] and lipopolysaccharide-induced oxidative stress [35]. Al Saadi et al [25 ]reported that montelukast decreased the ROS production in the whole blood and in isolated human polymorphonuclear neutrophils in asthmatic children.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Additionally, animal studies show that montelukast has a beneficial effect on oxidative stress-mediated conditions, such as ischemia-reperfusion injury, drug intoxication, and lipopolysaccharide-induced oxidative stress. [18][19][20][21] Al Saadi reports that montelukast decreases ROS production in whole blood and isolates human polymorphonuclear neutrophils in asthmatic children. 22 However, our recent study showed that montelukast monotherapy does not overcome the oxidative stress produced by asthma in children.…”
Section: Discussionmentioning
confidence: 99%
“…Gad et al found that MNK (10 and 20 mg/kg) can reduce cisplatin‐induced nephrotoxicity in rats by decreasing apoptosis (Gad, El‐Raouf, El‐Sayeh, Fawzy, & Abdallah, ). Also, another study showed that MNK can prevent gentamycin‐induced nephrotoxicity in rats (Otunctemur et al, ). However, Otunctemur et al did not examine the effects of MNK alone on rats.…”
Section: Discussionmentioning
confidence: 99%